Dose effect of oral Saccharomyces boulardii treatments on morbidity and mortality in immunosuppressed mice - Peret Filho, L. A.; Penna, F. J.; Bambirra, E. A.; Nicoli, J. R. (Journal of Medical Microbiology, 1998)
Survival, weight loss, translocation and histological alterations in the terminal ileum, liver and spleen were studied in mice simultaneously immunosuppressed with cyclophosphamide and treated or not with Saccharomyces boulardii until the death of all animals. The animals were divided into five groups: C1 (not immunosuppressed, not treated); C2 (immunosuppressed, not treated); B1 (immunosuppressed, treated with S. boulardii 10.0 mg); B2 (immunosuppressed, treated with S. boulardii 1.0 mg) and B3 (immunosuppressed, treated with S. boulardii 0.1 mg). Survival was higher in group B3 than in the other immunosuppressed groups. Weight loss was observed for all groups except C1. By day 7, some animals from each group were killed by ether inhalation for the determination of bacterial translocation and histopathological examination. Bacterial translocation to the liver was lower in groups C1 and B3 than in the other groups. The highest translocation to the liver and spleen was observed in group B1. Low S. boulardii translocation was observed in some animals, principally to the mesenteric lymph nodes. Histopathological examination showed a decrease in epithelial cell turnover with villus length reduction and loss of brush borders in group C2. Relative protection against these alterations was obtained when the animals were treated with the yeast, independently of the dose. Higher expression of the lymphoid component was also noted in the ileal lamina propria, liver and spleen of mice treated with the yeast, together with activation of the reticulo-endothelial system, when compared with group C2 where lymphocyte depletion was observed. This study suggests a relative protection of immunosuppressed animals by treatment with S. boulardii, but this phenomenon was inversely proportional to the yeast dose.